Bullying behaviour and psychosocial health among school students in New South Wales, Australia: cross sectional survey. Issue 7206 (7th August 1999) - Forero, Roberto; McLellan, Lyndall; Rissel, Chris; Bauman, Adrian
Abstract: Objectives: To examine the prevalence of bullying behaviours in schoolchildren and the association of bullying with psychological and psychosomatic health. Design: Cross sectional survey. Setting: Government and non-government schools in New South Wales, Australia. Participants: 3918 schoolchildren attending year 6 (mean age 11.88 years), year 8 (13.96), and year 10 (15.97) classes from 115 schools. Main outcome measures: Self reported bullying behaviours and psychological and psychosomatic symptoms. Results: Almost a quarter of students (23.7%) bullied other students, 12.7% were bullied, 21.5% were both bullied and bullied others on one or more occasions in the last term of school, and 42.4% were neither bullied nor bullied others. More boys than girls reported bullying others and being victims of bullying. Bullying behaviour was associated with increased psychosomatic symptoms Bullies tended to be unhappy with school; students who were bullied tended to like school and to feel alone. Students who both bullied and were bullied had the greatest number of psychological and psychosomatic symptoms. Conclusions: Being bullied seems to be widespread in schools in New South Wales and is associated with increased psychosomatic symptoms and poor mental health. Health practitioners evaluating students with common psychological and psychosomatic symptoms should consider bullying and the student's school environment as potential causes.